Kidney. (January 2016) - Hart, A.; Smith, J. M.; Skeans, M. A.; Gustafson, S. K.; Stewart, D. E.; Cherikh, W. S.; Wainright, J. L.; Boyle, G.; Snyder, J. J.; Kasiske, B. L.; Israni, A. K.
ABSTRACT: Kidney transplant provides significant survival, cost, and quality‐of‐life benefits over dialysis in patients with end‐stage kidney disease, but the number of kidney transplant candidates on the waiting list continues to grow annually. By the end of 2014, nearly 100, 000 adult candidates and 1500 pediatric candidates were waiting for kidney transplant. Not surprisingly, waiting times also continued to increase, along with the number of adult candidates removed from the list due to death or deteriorating medical condition. Death censored graft survival has increased after both living and deceased donor transplants over the past decade in adult recipients. The majority of the trends seen over the past 5 years continued in 2014. However, the new allocation system was implemented in late 2014, providing an opportunity to assess changes in these trends in the coming years.